Treatise on Instrumentation - Berlioz, Hector 1803-1869; Strauss, Richard 1864-1949; Front, Theodore 1909-2003 (New York Dover publications, 1991)
The most influential work of its kind ever written, appraising the musical qualities and potential of over 60 commonly used stringed, wind and percussion instruments. With 150 illustrative full-score musical examples from works by Berlioz, Mozart, Beethoven, Gluck, Weber, Wagner, and others, and numerous smaller musical examples. Complete with Berlioz' chapters on the orchestra and on conducting. Translated by Theodore Front. Foreword by Richard Strauss. Glossary.